Rasionalitas Kebijakan Desentralisasi Pendidikan di Provinsi Lampung (Kenyataan dan Harapan) - Rosalia, Feni; Kagungan, Dian (PERSPEKTIF, 2024)
This research uses Max Weber's theory of rationality to describe the reality, hopes, and rationality of educational decentralization, which are included in the rational category or vice versa. Data was collected through interviews, and observations related to the phenomenon of reality, hopes, and rationality of educational decentralization in Lampung Province and analyzed qualitatively. The research results show that in reality, the education decentralization policy in Lampung Province is rational. Based on instrumental theory, guaranteed education costs (free school), educational infrastructure and educational scholarships can support the ability of decentralization policies. Rationality in the value at which individuals decide to continue or not to continue their education is relatively stable at the basic education level in Lampung province. In the affective rationale, the conditions between individual objects of education such as students and teachers are the spearhead of education at the lower level. Education personnel must shape the character of their students in line with freedom of learning in the world of education. However, traditional rationality, namely custom, ethnicity and religion, does not influence education decentralization policies. The hope for the future is that the decentralization of education in Lampung Province requires strengthening each region's commitment so that progressive education is implemented evenly and cannot be separated from the responsibility of the regional government.